Eigenvalues of the QCD Dirac operator at finite temperature and density - Bittner, Elmar; Lombardo, Maria Paola; Markum, Harald; Pullirsch, Rainer (Arxiv, 2000)
We investigate the eigenvalue spectrum of the staggered Dirac matrix in two-color QCD at nonzero temperature and at baryon density when the eigenvalues become complex. The quasi-zero modes and their role for chiral symmetry breaking and the deconfinement transition are examined. The bulk of the spectrum and its relation to quantum chaos is considered. Comparison with predictions from random matrix theory is presented.